2005-06 Farm Bill Survey: Florida Producer Views on Farm Programs and Budget Priorities, Commodity Programs and Risk Management Policy - Rodney L. Clouser (EDIS)
FE666, a 5-page fact sheet by Rodney L. Clouser, is fourth in a series that describes the attitudes and opinions of Florida farm producers toward legislation that may be considered as the U.S. Congress debates the next farm bill. Published by the UF Department of Food and Resource Economics, December 2006.